METHODOLOGY FOR DEVELOPING CHEMISTRY TEACHERS’ FOREIGN LANGUAGE PROFESSIONAL COMMUNICATIVE COMPETENCIES: Study of methods for developing foreign language communication skills of university chemistry students - Kenzhe, Aziza; Bitemirova, Aliya; Shagrayeva, Bibigul; AKKUṢ, H.; ZHORABEKOVA, A. (Pedagogy and Psychology, 2024)
This study’s significance lies in its the need to develop foreign language professional communicative competence (FLPCC) of non-linguistic university students and the exploration of ways to achieve it. Developing FLPCC embodies not only speaking fluently in a foreign language in the professional field but also enhancing linguistic and communicative skills alongside subject knowledge. The purpose of this research is to identify effective methods and approaches for fostering fluent communication skills within the context of teaching chemistry in English. Analysis of the diverse methods of developing FLPCC enables us to reveal the components of this competence and create a set of exercises based on Kunanbaeva’s modelling. To evaluate the effectiveness of this set of exercises used in class organization, diagnostic monitoring was conducted. The findings obtained from the final exam revealed that the students enhanced their professional communicative skills, expanded their vocabulary, and were motivated to further develop their linguistic skills. These research findings are beneficial for young scientists, teachers, and students conducting research in this field.